Arthropod Daily Visits to Zinnia elegans and Ruellia tuberosa in Megaluh District - Anggun Wulandari; Mohammad Badrut Tamam (AGARICUS: Advances Agriculture Science & Farming, 2021)
Arthropod daily visits were seen from how often the Arthropod family visited the refugia plants of Zinnia elegans and Ruellia tuberosa species which were determined based on the Arthropod average per hour observed. This study aims to (1) find out what arthropods are found in Zinnia elegans and Ruellia tuberosa in Megaluh District, (2) find out the frequency of daily visits of arthropods to Zinnia elegans and Ruellia tuberosa plants in Megaluh District. This research is an exploratory descriptive study with a quantitative approach. This research was conducted in February 2021. Determination of the sampling point (sampling) was determined using the purposive sampling technique. The technique of collecting data is by collecting data using the visual control method at a distance of 2 meters at 06.00-07-00, 11.00-12.00, and 16.00-17.00. The data analysis technique was using SPSS paired t-test (pair-sample t-test). The results showed 22 families were found consisting of Paradoxosomatidae, Calliphoridae, Formicidae, Salticidae, Muscidae, Pentatomidae, Apidae, Vespidae, Flatidae, Gryllidae, Chrysomelidae, Crambidae, Hesperiidae, Stratiomyidae, Oxypidae, Coenagrionidae, Mantidae, Alyphecidae, Coccinellidae, Coccinellidae. , Pieridae. The highest average daily visitation frequency for Zinnia elegans was the Formicidae family with an average daily visit frequency of 8.5556 individuals/hour, while the highest family Ruellia tuberosa was also the Formicidae family with an average of 14.3333 individuals/hour. In Zinnia elegans and Ruellia tuberosa based on t-test, the significance level (2-tailed) was significant in the Pentatomidae family with a significance value of 0.003.